2021
DOI: 10.1186/s40478-021-01193-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic inactivation of SARM1 axon degeneration pathway improves outcome trajectory after experimental traumatic brain injury based on pathological, radiological, and functional measures

Abstract: Traumatic brain injury (TBI) causes chronic symptoms and increased risk of neurodegeneration. Axons in white matter tracts, such as the corpus callosum (CC), are critical components of neural circuits and particularly vulnerable to TBI. Treatments are needed to protect axons from traumatic injury and mitigate post-traumatic neurodegeneration. SARM1 protein is a central driver of axon degeneration through a conserved molecular pathway. Sarm1−/− mice with knockout (KO) of the Sarm1 gene enable genetic proof-of-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 96 publications
3
27
0
Order By: Relevance
“…A single impact closed head TBI model was used to produce traumatic axonal injury in the CC that models traumatic axonal injury in human TBI pathophysiology [ 7 , 50 , 54 , 55 , 72 , 84 ]. An Impact One Stereotaxic Impactor (Leica Biosystems, Buffalo Grove, IL) attached to a steel impactor with a 3-mm flat tip with rounded edges (Cat# 2520-3S, Neuroscience Tools, Aurora, IL) was zeroed on the surface of the skull centered at bregma (0 ML, 0 AP, 0 DV).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A single impact closed head TBI model was used to produce traumatic axonal injury in the CC that models traumatic axonal injury in human TBI pathophysiology [ 7 , 50 , 54 , 55 , 72 , 84 ]. An Impact One Stereotaxic Impactor (Leica Biosystems, Buffalo Grove, IL) attached to a steel impactor with a 3-mm flat tip with rounded edges (Cat# 2520-3S, Neuroscience Tools, Aurora, IL) was zeroed on the surface of the skull centered at bregma (0 ML, 0 AP, 0 DV).…”
Section: Methodsmentioning
confidence: 99%
“…Isoflurane administration was terminated immediately prior to impact. Our prior studies have shown that these parameters induce mild-moderate closed skull TBI with CC pathology that progresses to late stage CC atrophy without gross tissue damage or microhemorrhages, detected by neuropathology or magnetic resonance imaging [ 7 , 50 , 54 , 84 ]. Sham mice followed identical procedures but did not receive the impact.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Injured or diseased axons initiate a self-destruction program known as Wallerian degeneration. SARM1 triggers this pathological axon degeneration (1), and is a key driver of pathology in models of chemotherapy-induced peripheral neuropathy (2)(3)(4)(5), traumatic brain injury (6)(7)(8)(9)(10), glaucoma (11), and retinal degeneration (12,13). SARM1 also participates in antiviral defense.…”
Section: Introductionmentioning
confidence: 99%